Effect of Arbuscular Mycorrhiza on Oil Palm Seedling Growth and Development of Basal Stem Rot Disease Caused by Ganoderma Boninense - Maria Viva Rini (2001)
Basal stem rot (BSR) caused by Ganoderma species is the most serious disease of oil palm. Infection by the fungi causes significant loss in yield, often resulting in the palm's death as the disease progressed. Oil palm is a mycotrophic plant. Under natural conditions, the plant is often colonized by arbuscular mycorrhizal (AM) fungi. The current study carried out aimed to evaluate the role of AM in enhancing growth and development of oil palm seedlings and to examine the possibility of using this fungi as a biocontrol agent against basal stem rot (BSR) disease caused by G. boninense. A greenhouse trial was carried out to determine the optimum AM inoculum density for maximum plant growth and AM root colonization. The palms were inocu lated with 6 levels of AM inoculum (m ixed species of AM spores, extramatrical hyphae and infected root segments of Setaria ancep) viz. 0, 20, 40, 60, 80 and 100 g inoculum/plant. Resu lts obtained showed that 40 g inoculum/plant gave maximum growth and percent AM root colonization at 3 months after inoculation. This inoculum level was subsequently used in further experiments. A study was conducted to evaluate the effect of AM on plant growth and development. AM association significantly enhanced palm growth in terms of plant height, total leaf area and dry matter production. Physiological processes such as relative water content, photosynthetic rate and total root phenolic contents were also significantly improved through AM symbiosis. In contrast, stomatal resistance was significantly decreased. AM formation also alters root morphological characteristics. The effect was more profound in the tertiary roots . N umber and length of tertiary roots were respectively 63-105% and 26-113% higher in mycorrhizal than in control palms.